Challenges in Designing Games with a Purpose for Arabic Coreference Annotation - Wateen ALIADY; Massimo POESIO (Communications of International Proceedings, 2024)
This paper discusses several challenges we faced when creating Stroll-with-a-Scroll, a 3D game with the purpose of collecting Arabic coreference annotations. The game necessitated hiding composite annotation tasks and coreference annotation with orthogonal game elements without compromising the quality of the data gathered. Additionally, the balance between graphical richness and gaming performance presented further difficulties. Furthermore, one category of issues had to do with Arabic input words that are broken down into separate morphological units during pre-processing because in Arabic, as in other Semitic languages as well as languages such as Italian, Romanian, Spanish and Turkish, entity mentions can be morphologically incorporated in a word. When separated they might have a negative effect on the text’s readability. The last two issues have been resolved, although, an answer is still waiting for the first challenge.
Keywords: Games with a Purpose; Natural Language Processing; Coreference Annotation; 3D Virtual World Game; Unity Game Engine